Cross section of ultrahigh-energy neutrinos: Estimation of the uncertanties due to parton distribution functions - Mosquera, Mercedes Elisa (2020)
In this work we analyze the effect of uncertainties in parton distribution functions upon the calculation of cross sections for ultrahigh-energy neutrinos. As a detector we choose C12. The elementary diagrams for the neutrino-proton and neutron interactions have been calculated at quark level using nuclear parton distribution functions and their corresponding error bars, as given by the Jyvaskyla group. The leptonic sector of the current-current interactions includes active-sterile neutrino mixing. From the calculated cross section we have set limits on the values of the mixing parameters.